2012
DOI: 10.1177/0886260512441260
|View full text |Cite
|
Sign up to set email alerts
|

Violence Reported by the Immigrant Population Is High as Compared With the Native Population in Southeast Spain

Abstract: Immigrants constitute a population vulnerable to the problem of violence. This study sought to ascertain the prevalence of violence reported by the immigrant population in the Murcian Region of Spain and characterize the related factors, taking the country population as reference. A cross-sectional study was carried out based on a representative population sample of Latin American (n = 672; 48% women), Moroccan (n = 361; 25% women), and Spanish origin (n = 1,303; 66% women), aged 16 to 64 years. Using a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
3
21
0
4
Order By: Relevance
“…Other variables significantly related to having experienced IPV were, in women, a lower educational level, and experiences of discrimination; in men, a worse self-perceived health status were more frequently reported by those who had been victims of IPV. These factors had previously been reported by other authors studying IPV in different population settings, which underpins their strong role in determining IPV and their potential relevance for policies on IPV prevention [14,26,29,[31][32][33]. However, given the crosssectional design of most studies, the directionality of the associations between IPV and the above-mentioned factors cannot be properly established.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other variables significantly related to having experienced IPV were, in women, a lower educational level, and experiences of discrimination; in men, a worse self-perceived health status were more frequently reported by those who had been victims of IPV. These factors had previously been reported by other authors studying IPV in different population settings, which underpins their strong role in determining IPV and their potential relevance for policies on IPV prevention [14,26,29,[31][32][33]. However, given the crosssectional design of most studies, the directionality of the associations between IPV and the above-mentioned factors cannot be properly established.…”
Section: Discussionmentioning
confidence: 79%
“…Ansara et al [3] reported that men and women older than 15 years participating in the 2004 Canadian General Social Survey were similarly likely to experience less severe forms of physical aggression or psychological abuse. More recently, previous results from the authors on a representative sample of immigrant population living in a South-Eastern Spanish region showed a similarly low prevalence of IPV in Latin-American women (2 %) and men (1 %) [26]. A previous meta-analysis on gender-based differences of physical aggression among heterosexual partners revealed that women used certain types of physical aggression even more frequently than men, although men were more likely to cause injuries to their partners [27].…”
Section: Discussionmentioning
confidence: 85%
“…More specifically, immigrant couples coming from majority-Muslim countries show higher IPV rates if compared to their non-immigrant counterparts: for example, Moroccan immigrant women in Spain (Colorado-Yohar et al, 2012), Iraqi (Barkho, Fakhouri, & Arnetz, 2011), as well as Pakistani and South-Asian (Adam & Schewe, 2007; Lee & Hadeed, 2009) women immigrated to the U.S. report being exposed to abusive behaviors to a greater extend if compared to the native population and even to other non-immigrant Muslim women.…”
mentioning
confidence: 99%
“…La metodología se ha descrito en otro estudio. 12 Brevemente, se dividió a la población inmigrante en 12 estratos, según origen, sexo y edad, que agrupaban los centros de salud de la RM de acuerdo con su diferente composición de población inmigrante. La selección de los centros de salud (conglomerados) dentro de cada estrato se realizó con probabilidad proporcional al número de inmigrantes de cada centro en ese estrato.…”
Section: Muestraunclassified